PENGARUH BIAYA PROMOSI TERHADAP PENDAPATAN JASA “NAKAMURA HOLISTIC THERAPY” DI SURAKARTA - Sartono Maya Saputra; Retno Ibut Utami (ProBank, 2017)
Promotion and communication are summarized in the promotional mix that contains a combination of the best strategy of the variable cost of advertising, the cost of personal selling and sales promotion costs, all of which are planned to achieve the objectives of the sales program: increasing service revenues in order to increase as well jumlahl aba obtained. this study aims to determine the effect of promotional costs consist of: the cost of advertising, sellling personal cost, and cost of sales promotions on services revenue. The data used in this research is data based on time series (time series). This research is explanatory research, ie research that explains the causal relationship between research variables through hypothesis testing. The analytical tool used in this research is multiple linear regression analysis. The study shows that the variable cost of advertising and sales promotion variable is not significant positive effect on service revenues. While the cost of personal selling significant negative effect on service revenues. Advertising, personal selling, and sales promotion together a significant effect on service revenues.Keywords: Advertising Costs, Fees Personal sellling, Cost of Sales Promotion, Revenue Services